Development and Evaluation of Poorly Water-Soluble Celecoxib as Solid Dispersions Containing Nonionic Surfactants Using Fluidized-Bed Granulation - Hyeok Jin Kwon; Eun-Ji Heo; Young-Hwan Kim; Sarah Kim; Young-Ha Hwang; Ji-Mi Byun; Se Hyeop Cheon; Sang Yeob Park; Dong Yun Kim; Kwan Hyung Cho; Han-Joo Maeng; Dong-Jin Jang (MDPI AG, 2019)
The purpose of this study is to develop a solid dispersion system with improved dissolution, absorption, and patient compliance of poorly water-soluble celecoxib (CXB). Instead of sodium lauryl sulfate (SLS), an anionic surfactant used in the marketed product (Celebrex®), solubilization was performed using non-ionic surfactants with low toxicity. Cremophor RH40 (Cre-RH) was selected as the optimal solubilizer. Granules and tablets containing CXB and Cre-RH were prepared via fluid-bed and tableting processes, respectively. The morphology, crystallinity, flowability, dissolution, and pharmacokinetics for CXB-solid dispersion granules (SDGs) and the hardness and friability for CXB-solid dispersion tablets (SDTs) were evaluated. The solubility of CXB was found to be increased by about 717-fold when using Cre-RH. The dissolution of granules containing Cre-RH was found to be increased greatly compared with CXB API and Celebrex® (66.9% versus 2.3% and 37.2% at 120 min). The improvement of the dissolution was confirmed to be the same as that of granules in tablets. The CXB formulation resulted in 4.6- and 4.9-fold higher AUCinf and Cmax of CXB compared with those of an oral dose of CXB powder in rats. In short, these data suggest that the solid dispersion based on Cre-RH—a non-toxic solubilizer, non-ionic surfactant— may be an effective formulation for CXB to enhance its oral bioavailability and safety.